Further selections from the tragic history of the sea, 1559-1565 : narratives of the shipwrecks of the Portuguese East Indiamen Aguia and Garça (1559), São Paulo (1561) and the misadventures of the Brazil-ship Santo Antonio (1565) /: narratives of the shipwrecks of the Portuguese East Indiamen Aguia and Garça (1559), São Paulo (1561) and the misadventures of the Brazil-ship Santo Antonio (1565). (2017) - Brito, Bernardo Gomes de, 1688-1760?
No abstract available